N-acetylcysteine blocks SOS induction and mutagenesis produced by fluoroquinolones in Escherichia coli. (18th May 2019) - Rodríguez-Rosado, Ana I; Valencia, Estela Ynés; Rodríguez-Rojas, Alexandro; Costas, Coloma; Galhardo, Rodrigo S; Rodríguez-Beltrán, Jerónimo; Blázquez, Jesús
Abstract: Background: Fluoroquinolones such as ciprofloxacin induce the mutagenic SOS response and increase the levels of intracellular reactive oxygen species (ROS). Both the SOS response and ROS increase bacterial mutagenesis, fuelling the emergence of resistant mutants during antibiotic treatment. Recently, there has been growing interest in developing new drugs able to diminish the mutagenic effect of antibiotics by modulating ROS production and the SOS response. Objectives: To test whether physiological concentrations of N -acetylcysteine, a clinically safe antioxidant drug currently used in human therapy, is able to reduce ROS production, SOS induction and mutagenesis in ciprofloxacin-treated bacteria without affecting antibiotic activity. Methods: The Escherichia coli strain IBDS1 and its isogenic mutant deprived of SOS mutagenesis (TLS − ) were treated with different concentrations of ciprofloxacin, N -acetylcysteine or both drugs in combination. Relevant parameters such as MICs, growth rates, ROS production, SOS induction, filamentation and antibiotic-induced mutation rates were evaluated. Results: Treatment with N -acetylcysteine reduced intracellular ROS levels (by ∼40%), as well as SOS induction (by up to 75%) and bacterial filamentation caused by subinhibitory concentrations of ciprofloxacin, without affecting ciprofloxacin antibacterial activity. Remarkably, N -acetylcysteine completely abolished SOS-mediated mutagenesis. Conclusions: Collectively, our data strongly support the notion that ROS are a key factor in antibiotic-induced SOS mutagenesis and open the possibility of using N -acetylcysteine in combination with antibiotic therapy to hinder the development of antibiotic resistance.